The correlations between physical attributes and golf clubhead speed: A systematic review with quantitative analyses - Ehlert, A. (European Journal of Sport Science, 2021)
Clubhead speed (CHS) is a commonly assessed golf performance measure and has been demonstrated to increase in response to physical training. Knowledge of the physical attributes that correlate with CHS will aid in developing effective testing and training protocols for golfers. Thus, the purpose of this review was to identify studies that evaluated the correlation between physical attributes and CHS and synthesise the correlation coefficients using three-level meta-analytic methods. Physical attributes were categorised first by general physical attribute categories. Pooled correlations were also estimated for specific attributes (e.g. jump height, body mass) that were evaluated across three or more studies. The results suggested that CHS had the strongest correlations with measures of upper body power/explosiveness (r = 0.51, 95% confidence interval [95CI]: 0.34, 0.67), lower body strength (r = 0.46; 95CI: 0.27, 0.66), upper body strength (r = 0.41; 95CI: 0.18, 0.63), and lower body power/explosiveness (r = 0.38; 95CI: 0.23, 0.53). Muscle endurance (r = 0.18; 95CI: 0.07, 0.28) and anthropometrics (r = 0.27; 95CI: 0.12, 0.42) had small, but significant correlations, while flexibility (r = 0.03; 95CI: -0.08, 0.14) had a trivial correlation. Several specific assessments such as squat strength, estimated jump power, and medicine ball throw outcomes had large pooled correlations with CHS (r = 0.55-0.63). Overall, the results suggest that measures of muscle strength and power/explosiveness have moderate-large correlations with CHS. Flexibility measures did not have significant associations with CHS, but this may be a result of the specific measures used within the literature.